2020
DOI: 10.1002/lary.28850
|View full text |Cite
|
Sign up to set email alerts
|

Does the Expiratory Disproportion Index Remain Predictive of Airway Stenosis in Obese Patients?

Abstract: Objectives/Hypothesis The expiratory disproportion index (EDI) is the ratio of forced expiratory volume in 1 second divided by peak expiratory flow rate multiplied by 100. An elevated EDI (>50) can help differentiate upper airway stenosis from other dyspnea etiologies, but this has not been verified when considering body habitus. We hypothesize that the predictive value of elevated EDI in diagnosing airway stenosis will be lower in obese patients as compared to nonobese patients. Study Design Retrospective coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…Pulmonary function tests (PFTs) have proven reliable for diagnosis and differentiation of LTS from other pulmonary diseases through the use of the expiratory disproportion index (EDI), which is based on the ratio of forced expiratory volume in 1 s to peak expiratory flow rate [64]. The diagnostic utility of EDI in obese patients is reliable, albeit with a lower sensitivity than nonobese patients, making it less useful to rule out airway stenosis in this cohort [65]. This diagnostic test could potentially prevent delays in diagnosis.…”
Section: Diagnosis and Preoperative Evaluationmentioning
confidence: 99%
“…Pulmonary function tests (PFTs) have proven reliable for diagnosis and differentiation of LTS from other pulmonary diseases through the use of the expiratory disproportion index (EDI), which is based on the ratio of forced expiratory volume in 1 s to peak expiratory flow rate [64]. The diagnostic utility of EDI in obese patients is reliable, albeit with a lower sensitivity than nonobese patients, making it less useful to rule out airway stenosis in this cohort [65]. This diagnostic test could potentially prevent delays in diagnosis.…”
Section: Diagnosis and Preoperative Evaluationmentioning
confidence: 99%
“…Today, there’s a lack of evidence on the validity of the EDI as screening parameter for upper airway stenosis. To our knowledge, there are only two recent studies who reported on the diagnostic accuracy of the EDI for upper airway stenosis patients: Nouraei et al in 2013 and Calamari et al in 2020 [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second report on the EDI, of Calamari et al in 2020, focused on the influence of obesity on the diagnostic accuracy of the EDI as screening tool for upper airway stenosis [ 14 ]. They defined obesity as a BMI > 30 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations